Analysis of Fiqh Tabarru' on the Use of Cashback Gopay Coins in Buying and Selling Transactions in Tokopedia App - Agustiani, Sarah Amanah; Susilawati, Cucu (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2023)
Gopay coins are balances given by Tokopedia for every customer who purchases at Tokopedia by fulfilling the conditions set by Tokopedia. This study aims to determine the mechanism of revenue and use of GoPay coins and fiqh tabarru' analysis of GoPay coins cashback in buying and selling transactions at Tokopedia. The method used in this research is a case study. This study's results indicate that to get GoPay coins, users must follow the conditions set by Tokopedia. GoPay coins are a marketing strategy so that Tokopedia users continue to grow. The contract used in giving GoPay coins by Tokopedia to users is a grant contract, namely ja'izah tasyji'iyyah. In conclusion, using GoPay coins in buying and selling transactions in the Tokopedia application is permissible according to Sharia economic law and is included in the fiqh tabarru'.